ANALYSIS OF FACTORS AFFECTING TOTAL FINANCING ON ISLAMIC BANK IN INDONESIA FROM 2012-2015 - Diah Ayu Meganing Tyas (EKPI 16 UMY 248, 2016)
as CAR (Capital Adequacy Ratio), ROA(Return On Asset), ROE (Return On Equity), NPF (Non Performing Financing), Profit Share and Depositor Funds. Monthly secondary data are used starting from January 2012 up to Juny 2015. The research subject is to analyze the long-run and short-run of finance, CAR, ROA, ROE, NPF, profit share and depositor funds in islamic banking. Using VECM (Vector Error Correction Model). Theresults show the influences in short-term period, they are: CAR, depositor funds and profit share. The second result shows the influencesin financing in long-term period, they are:depositor funds influences financing negatively significant, variable NPF influences finance negatively significant, variable profit share influences finance positively significant and variable ROA influences finance positively significant.. Keywords: Financing in Islamic banks, VECM (Vector Error Correction Model), CAR, ROA, ROE, NPF, Profit Share and Depositor funds.